Studying Fiqh Based on the Quran and Hadith in the Modern Era by Revisiting the Methodology of Legal Istinbat - Mappasessu, Mappasessu; Akmal, Andi Muhammad (STAI Nurul Islam Mojokerto, 2025)
This study aims to re-examine the normative foundations of the Qur’an and Hadith as the primary sources of Islamic law in responding to contemporary social dynamics and legal challenges. The Qur’an is positioned as a sacred text that contains universal and eternal principles for all humankind, while the Hadith serves as a methodological guide for applying Qur’anic laws to present-day contexts. The study is grounded in the Ma‘na-Cum-Maghza theoretical framework, a contextual approach that emphasizes understanding the substantive meaning and message of the divine texts. This research adopts a qualitative method, employing literature review techniques from both classical and contemporary Islamic legal sources. The findings indicate the necessity for a renewed methodology of istinbat (legal reasoning) that is more responsive to social change, without neglecting the normative authority of Islamic legal sources. These findings are contextualized within the theoretical framework, highlighting the epistemological and methodological implications for the development of fiqh in Indonesia’s legal landscape. This study contributes originality by integrating the Ma‘na-Cum-Maghza approach with istinbat methodology, thereby enriching the discourse of contemporary Islamic legal studies and offering a new direction for lawmaking grounded in maqashid shariah and social justice. The findings provide practical insights for academics, practitioners, and policymakers in the field of Islamic law.